Kiribati economic survey: Oceans of opportunity. Issue 1 (12th February 2020) - Webb, James
Abstract: Kiribati is one of the poorest and most remote Pacific nations but has the largest productive tuna fishery. The Vessel Day Scheme implemented in 2012 led to unprecedented growth in fishing revenue between 2012 and 2015, with similarly unprecedented expansion of government expenditure from 2016 to 2019. For the first time in its history, the Kiribati Government, rather than any foreign development partner, is the single largest financier of public investment. Whereas the general economy and government finances have benefited greatly from the fisheries boom, questions have been raised around recent government spending and how long there will be the fiscal space to support such discretionary decisions in the context of rapidly increasing operating costs. Fishing revenue alone will not be enough to fundamentally shift the development trajectory of the Kiribati people. A new period of reform is needed.